Toxoplasmosis as a factor in chronic diseases in dogs - M. Broshkov; V. Kusturov (Kazimierz Wielki University, 2022)
Toxoplasmosis is one of the most common animal and human diseases worldwide and is reported in European, Asian, African, North, and Latin American countries. This is due to the limited research methods that confirm the pathogen presence in animals and humans, the characteristic clinical signs, in some regions it is associated with sanitation problems, mainly due to improper cooking as most positive animals did not show a significant association with rodents or raw water consumption, the impossibility of complete body rehabilitation using currently known tools and treatment regimens, as well as the lack of understanding among individual physicians the peculiarities of pathogenesis in this pathology, features of diagnostic and therapeutic approaches. Toxoplasmosis course is clinically manifested by a wide range of clinical signs and immunosuppression of the cellular immune system that complicates the selection of pharmacological agents for the treatment in dogs. Prolonged functioning of the immune system in conditions of chronic recurrent infection contributes to cytokine imbalances and their permanent expression, supporting the inflammatory process. The reason for the development of chronic diseases is a violation of homeostasis due to either excessive intake of xenobiotics, including toxic, or violation of various levels of protection - detoxification, immunity, and excretion of pathological metabolites from the body Therefore, this review is aimed at providing an analysis on the clinical aspects of toxoplasmosis, the development of immunological reactions, and the seasonality of antigen activation, which coincides with the exacerbation of clinical signs. This review may be of interest among practicing physicians and researchers.